Produksi Bioetanol Dari Limbah Kulit Nanas Menggunakan Bakteri Clostridium Acetobutylicum Dengan Variasi Konsentrasi Inokulum Dan Penambahan Nutrisi - Sari, Nurriya Mayang; Muria, Sri Rezeki; Yenie, Elvi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One material that has potential as raw material for bioethanol is the pineapple peel. Pineapple peel is one of the biggest agricultural waste in Indonesia, especially in Riau derived from pineapples. Pineapple peel can be used as raw material for bioethanol production due to contains of fiber, carbohydrates and glucose. This study was conducted to produce ethanol by fermentation of pineapple peel slurry with treatment concentration inoculum at 10%, 12%, 14% and 16% with the addition nutrition of urea 0,6 g/l , ammonium sulphate 1,3 g/l and fermentation time of 2, 4, 6, 8 and 10 hours. The fermentation was conducted in batch process. The result showed that inoculum volume and substrate fermentation also ethanol increased since the population of cells improved.The highest yield of bioethanol is 9% (v/v) at inoculum concentred 14% with addition nutrition of urea and the fermentation time 8 hours.keywords : volatile acid, urea, amonium sulfate, fermentation.